Nanowire-based AFM-IR microscopy: Unveiling chemical structure at sub-10-nm resolution with silver nanowire–functionalized AFM probes - Yasuhiko Fujita; Mariko Takahashi; Farsai Taemaitree; Hiroshi Uji-i; Hirohmi Watanabe (Proceedings of the National Academy of Sciences, 2026)
Atomic force microscopy–based infrared (AFM-IR) microscopy has emerged as a powerful tool for nanoscale chemical imaging, combining the topographical precision of AFM with the molecular specificity of IR spectroscopy. However, its performance is still limited by conventional metal-coated AFM probes, which provide only modest near-field enhancement, ultimately restricting both spatial resolution and chemical sensitivity. In this work, we present a nanowire-based AFM-IR approach that overcomes these limitations by introducing a probe design: Chemically synthesized noble metal nanowires are affixed to the tip of a standard AFM cantilever. These nanowires support Fabry–Pérot resonances, functioning as mid-IR antennas that generate strongly confined optical near-field, thereby enhancing spatial resolution and sensitivity. The probe design also enables stable AFM-IR operation on both hard and soft materials. We demonstrate significantly improved imaging and spectroscopic performance, achieving spatial resolution below 10 nm and sensitivity at the submonolayer level. These findings establish nanowire-based AFM-IR microscopy as a highly promising platform for superresolution vibrational spectroscopy, with broad applications ranging from soft matter and two-dimensional materials to biomolecular analysis.